Thermal regime of the lithosphere and geothermal potential in Xiong'an New Area. Issue 2 (March 2019) - Wang, Zhuting; Jiang, Guangzheng; Zhang, Chao; Hu, Jie; Shi, Yizuo; Wang, Yibo; Hu, Shengbiao
Investigation into the thermal regime of lithosphere is an essential part of geothermal research. The thermal state of lithosphere can be expressed as the vertical distribution of temperature. It has been found that the thermal regime of lithosphere can control the heat flow distribution and the geothermal mechanism of local geothermal fields. In this work, equilibrium temperature logs were obtained from 27 wells, and thermal conductivity and heat generation data were collected from 148 rock samples from different wells. Besides, 55 high-quality terrestrial heat flow values were extracted. Based on these data, the distribution of heat flow across Xiong'an New Area was mapped. Later, the thickness of the thermal lithosphere in Xiong'an and the deep crustal temperature were analyzed using the one-dimensional steady-state heat conduction equation. The crustal structure beneath this area was derived from the seismic wave velocity profile, and it was then used to illustrate the connection between the geothermal fields' heat sources and regional tectonic setting. The results indicate that high heat flow is mainly distributed around the basement uplifts, such as Niutuozhen uplift and Rongcheng uplift. The average heat flux in the study area is 70.5 mW/m 2, higher than the 61.5 mW/m 2 in mainland China. The temperature-depth profiles show great temperature variation across the new area. At the depth of 40 km, the crustal temperature ranges from about 750°C to 1100°C. Despite the large temperature variation, this area shows high thermal state. The temperature variation with depth may be attributed to the heat flow variability and the high thermal state may be caused by the large residual heat flow from the lithosphere boundary. The average reduced heat flow in the new area is high at around 44.35mW/m 2, which is associated with the high thermal state of this area.